ASSESSMENT OF VISITORS TO THE COMPONENTS OF THE ASIA FARM PEKANBARU TOURISM PRODUCTS - Saputra, Diki Wahyudi; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of study to determine how the assessment of visitors to the components of the Asia Farm Pekanbaru tourism products. The research use quantitative descriptive mothod to analyze the prooblems. The sampel inside this research are 100 respondence by using slovin. And then technique to collected data in this research are using observation, questionnaire, and documentation. And it was using descriptive  data analysis techniques. The components that become a visitors assessment are attraction, accessibilitity, amenities and networking (Manson dan Poerwanto in Nih Luh Henny Andayani, 2013:3). From the result of research, the components of Asia Farm tourism products have met the standards and all types of attractions have something to the attention of visitors, other than that the facilities are available properly so that visitors will feel comfortable whe using these facilities. As well as very easy access when traveling to make visitors not spending too big a budget, to Asia Farm tourism object management offers cooperation to visitors who want to carry out certain events.Key word : Components tourism product, assessment of visitors,Tourist Attraction